Thermal characterization and thermal tuning in nanostructured materials - Majid Kabiri Samani (2015)
In this dissertation, the experimental investigation of the heat transport in crystalline nanostructured materials is studied. Different methods to reduce their thermal conductivity to create user-specific materials are presented as well. It is shown that by using different methods such as the incorporation of additional elements in the crystalline structure, controlling the deposition and embedding metallic nanoinclusions in the semiconductor matrix, it is possible to reduce the thermal conductivity. Thermal conductivity measurements have been conducted by using pulsed photothermal reflectance (PPR) and 3ω techniques at room temperature. The materials studied in this work include Ti-based hard coatings, multilayer TiN/TiAlN coatings and n-type Bi2Te2.7Se0.3 thermoelectric films. Firstly, the effect of the incorporation of Al on the thermal conductivity of TiAlN coatings prepared by a lateral rotating cathode arc (LARC) technique has been investigated. To study this, a series of TiAlN coatings were deposited on stainless steel substrates and the thermal conductivity of the coatings was measured by the PPR technique. The Microstructure of the coatings was analyzed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). These techniques reveal that TiN coating shows a clear columnar structure with a predominant (111) preferential orientation. With the incorporation of Al, the columnar structure of the coatings is disrupted, the grain size of the coatings is decreased and the dislocation density is increased. A significant decrease in thermal conductivity was found with increasing Al content and a minimum thermal conductivity of about 4.63 W/mK was obtained at the Al/Ti atomic ratio of around 0.72. The decrease in thermal conductivity of the TiAlN coatings is explained in terms of increased phonon scattering due to the decrease in the grain size and increasing dislocation density. The effect of the incorporation of Al and Si on the thermal conductivity of the TiAlSiN nanocomposite coatings prepared by the LARC technique has been studied. A series of TiAlSiN nanocomposite coatings were deposited on stainless steel substrates and the room temperature thermal conductivity of the coatings was measured by the PPR technique. A significant decrease in thermal conductivity was found with increasing Al and Si contents and it was shown that the thermal conductivity of the TiAlSiN nanocomposite coatings is about 1.8 W/mK at a (Al+Si)/Ti atomic ratio of around 1.76. The decrease in thermal conductivity of the TiAlSiN nanocomposite coatings can be attributed to the reduced grain size and the formation of a nanocomposite structure which consists of crystalline nanograins embedded in a disordered, lower thermal conductivity than TiAlN, amorphous SiNx matrix. In order to study the effect of a multilayer structure on the thermal conductivity, a series of multilayer [TiN/TiAlN]n coatings with different bilayer numbers n were deposited on stainless steel substrates by the LARC technique. The PPR technique was employed to measure thermal conductivity of the coatings at room temperature. TEM observation and microstructure analysis of multilayer coatings show a lattice mismatch and misfit dislocations at the interfaces between TiN and TiAlN layers, and a decrease of the grain size with increasing number of layers. Results show that the thermal conductivity of the multilayer coatings reduces with increasing bilayer number n. Phonon scattering is increased at the interfaces and grain boundaries due to the existence of misfit dislocations and to the decreasing grain size, respectively. For the study of the effect of metallic nanoinclusions in thermoelectric (TE) film on the thermal conductivity, textured n-type Bi2Te2.7Se0.3 thin films with Pt nanoinclusions were successfully prepared via pulsed laser deposition. The thermal conductivity of the TE films was measured by the 3ω technique. The TEM observation shows that the Pt nanoinclusions are embedded at the grain boundaries of the semiconductor matrix. By introducing Pt nanoinclusions, the thermal conductivity is reduced due to scattering phonon at the grain boundaries.